2012
DOI: 10.1021/nn2040389
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Confinement of Electromagnetic Hot and Cold Spots in Gold Nanocubes

Abstract: We report a near-field imaging study of colloidal gold nanocubes. This is accomplished through a photochemical imaging method in which molecular displacements are vectorial in nature, enabling sensitivity to the polarization of the optical near-field of the nanocubes. We analyze the confinement of both electromagnetic hot and "cold" spots with a resolution of λ/35 and emphasize the particularly high spatial confinement of cold spots. The concept of a cold spot complements the well-known electromagnetic hot spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 51 publications
2
98
0
Order By: Relevance
“…These photoexcited electrons directly get injected into the nearby TiO 2 CB due to the formation of Schottky barrier at the metal semiconductor interface. It was also suggested that the hot spots (plasmon decay producing intensely hot electrons) appear on the sharp edges and corners of TiO 2 where the electric field intensity of SPR is several times higher than that of the incident electric field of the photon [201][202][203][204]. Electron hole pairs are generated by surface plasmon decay and the rate of generation is intensified by the local filed enhancement on the hot spot regions (Fig.…”
Section: Photocatalytic Activity Of Palladium Deposited Titania (Pd/tmentioning
confidence: 99%
“…These photoexcited electrons directly get injected into the nearby TiO 2 CB due to the formation of Schottky barrier at the metal semiconductor interface. It was also suggested that the hot spots (plasmon decay producing intensely hot electrons) appear on the sharp edges and corners of TiO 2 where the electric field intensity of SPR is several times higher than that of the incident electric field of the photon [201][202][203][204]. Electron hole pairs are generated by surface plasmon decay and the rate of generation is intensified by the local filed enhancement on the hot spot regions (Fig.…”
Section: Photocatalytic Activity Of Palladium Deposited Titania (Pd/tmentioning
confidence: 99%
“…More recently, azopolymers have been employed to map the optical near fields around various types of metal nanostructures . Typically, a thin azopolymer layer is spin coated onto a plasmonic array, and the topographic modification upon irradiation is observed to closely follow the near‐field intensity distribution around the structures .…”
Section: Photochemical Imaging Of Optical Near Fieldsmentioning
confidence: 99%
“…The IPCE enhancement ratio graph clearly shows photocurrent enhancement in the 550-800-nm region of the spectrum, corresponding to the LSPR of the popcorn-shaped metal NPs (Figure 18). Au@SiO 2 nanocubes were found advantageous over spherical NPs in DSCs, as they had two times higher extinction and absorption efficiency, two times larger surface area, and higher electromagnetic field localization at edges and corners [49,30,98,99]. The edge length of Au nanocubes can be adjusted by hexadecyltrimethylammonium bromide (CTAB) ligands [100].…”
Section: Anisotropic Metal Nanostructuresmentioning
confidence: 99%